A positive electrode material and its preparation method and application

By applying Cr2O3 and NiTiO3 coating modification of the ternary positive electrode material of lithium-ion batteries, the capacity and cycle stability problems caused by the increase of nickel content are solved, and the battery performance is significantly improved.

CN118899427BActive Publication Date: 2025-03-04ZHUJI PAWA NEW ENERGY CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411396649.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-03-04
Estimated Expiration
2044-10-09

AI Technical Summary

Technical Problem

With the increase in the nickel content of the ternary positive electrode material of lithium-ion batteries, the capacity and cycle stability of the battery are affected.

Method used

By using Cr2O3 and NiTiO3 to coat and modify the positive electrode material, the structural stability of the high-nickel positive electrode material is enhanced, and a simple and controllable process promotion and marketization are promoted and marketed through the preparation method.

Benefits of technology

It improves the cycle stability and electrochemical performance of the battery, enhances the structural stability of the positive electrode material, reduces the possibility of the cladding falling off, and improves the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118899427B_ABST
    Figure CN118899427B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of lithium-ion battery materials, and discloses a positive electrode material and a preparation method and application thereof. The positive electrode material comprises a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least part of the surface of the substrate, and the second coating layer is coated on at least part of the surface of particles formed by the substrate and the first coating layer; the chemical formula of the substrate is LiNi x Co y Mn 1‑x‑y O2, 0.7≤x<1, 0≤y≤0.2, 0<1‑x‑y≤0.3; the first coating layer is Cr2O3; the second coating layer is NiTiO3, and the positive electrode material is coated and modified by NiTiO3 and Cr2O3, which is beneficial to maintain high capacity and improve the cycle stability of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of lithium ion battery materials, and in particular relates to a positive electrode material and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries have the characteristics of high energy density, long service life, low self-discharge rate, and no memory effect. 1-x-y Co x M y O2 has the advantages of high specific capacity and low price. 1-x-y Co x M y The specific capacity of O2 is closely related to the nickel content. As people's requirements for the energy density of lithium-ion batteries are getting higher and higher, the nickel content of ternary positive electrode materials is also increasing. However, as the nickel content of ternary positive electrode materials increases, the capacity and cycle stability of the battery are affected to a certain extent. Summary of the invention

[0003] In view of the defects and shortcomings of the prior art, in the first aspect, the present invention provides a positive electrode material; in the second aspect, the present invention provides a method for preparing the positive electrode material; in the third aspect, the present invention provides a battery.

[0004] In a first aspect, the present invention provides a positive electrode material, comprising a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a portion of the surface of the substrate, and the second coating layer is coated on at least a portion of the surface of particles formed by the substrate and the first coating layer; the chemical formula of the substrate is LiNi x Co y Mn 1-x-y O2, 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3; the first coating layer is Cr2O3; the second coating layer is NiTiO3.

[0005] Preferably, the positive electrode material LiNi x Co y Mn 1-x-y The mass ratio of O2, Cr2O3 and NiTiO3 is 1:0.4~2%:1~3%.

[0006] In a second aspect, the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0007] Step 1, mixing LiNi x Co y Mn 1-x-y O2 positive electrode material, chromium oxalate, and ethanol to obtain a slurry;

[0008] Step 2, heating the slurry until the ethanol is completely volatilized to obtain solid particles; drying the solid particles to obtain a precursor;

[0009] Step 3, grinding and mixing the precursor and the NiTiO3 material, and then calcining in an air atmosphere;

[0010] Among them, 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3.

[0011] Preferably, in step 1, the LiNi in the slurry x Co y Mn 1-x-y The mass ratio of the O2 positive electrode material to chromium oxalate is 1:1~5%.

[0012] Preferably, in step 2, the heating temperature is 50-150° C.; the drying temperature is 80-180° C., and the drying time is 1-10 hours.

[0013] Preferably, in step 3, the calcination temperature is 700-1200° C. and the calcination time is 1-5 h.

[0014] Preferably, in step 3, the LiNi in the precursor x Co y Mn 1-x-y The mass ratio of O2 and NiTiO3 is 1:1~3%.

[0015] Preferably, in step 3, the NiTiO3 material used is prepared by the following method: mixing and stirring Ni(CH3COO)2·4H2O, Ti(OC4H9)4 and ethylene glycol solution, centrifuging after a period of reaction, washing, drying and calcining the obtained solid matter.

[0016] Preferably, the molar ratio of the nickel element in Ni(CH3COO)2·4H2O and the titanium element in Ti(OC4H9)4 used to prepare the NiTiO3 material is 1:0.8-1.2.

[0017] Preferably, the drying temperature is 100-150° C. and the drying time is 10-15 hours.

[0018] Preferably, the detergent is ethanol.

[0019] Preferably, the calcination temperature is 600-1000° C., and the calcination time is 2-10 hours.

[0020] In a third aspect, a battery comprises the above-mentioned positive electrode material or the positive electrode material prepared by the above-mentioned preparation method.

[0021] Compared with the prior art, the present invention has the following obvious beneficial effects:

[0022] (1) The positive electrode material is modified by coating with NiTiO3 and Cr2O3. The structural advantages of the coating are used to enhance the structural stability of the high-nickel positive electrode material to resist structural changes during the charging and discharging process, which is beneficial to maintaining high capacity and improving the cycle stability of the battery. The catalytic effect of NiTiO3 can accelerate the transmission of ions and electrons, which is beneficial to the deintercalation and extraction of lithium ions, while Cr2O3 has a higher lithium storage capacity. The combination of the two can comprehensively improve the electrochemical performance of the battery.

[0023] (2) The preparation method provided by the present invention is simple and controllable, and is easy to promote and commercialize. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 Uncoated LiNi 0.9 Co 0.0.5 Mn 0.05 SEM image of O2;

[0025] Figure 2 This is a SEM image of the positive electrode material prepared in Example 1;

[0026] Figure 3 The positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2 and the uncoated LiNi 0.9 Co 0.0.5 Mn 0.05 Cycling performance test diagram of batteries assembled with O2. DETAILED DESCRIPTION

[0027] The present invention provides the following specific technical solutions.

[0028] In a first aspect, the present invention provides a positive electrode material, comprising a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a portion of the surface of the substrate, and the second coating layer is coated on a portion of the surface of particles formed by the substrate and the first coating layer; the chemical formula of the substrate is LiNi x Co y Mn 1-x-y O2, 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3; the first coating layer is Cr2O3; the second coating layer is NiTiO3.

[0029] The inventors modified the positive electrode material by coating it with multi-component materials, and used the structural advantages of the coating to enhance the structural stability of the high-nickel positive electrode material to resist structural changes during the charging and discharging process, which is beneficial to maintaining high capacity and improving the cycle stability of the battery. The catalytic effect of NiTiO3 can accelerate the transmission of ions and electrons, which is beneficial to the deintercalation of lithium ions, while Cr2O3 has a higher lithium storage capacity. The combination of the two can comprehensively improve the electrochemical performance of the battery.

[0030] The positive electrode material LiNi x Co y Mn 1-x-y The mass ratio of O2, Cr2O3 and NiTiO3 is 1:0.4~2%:1~3%.

[0031] In a second aspect, the present invention provides a method for preparing a positive electrode material, comprising the following steps:

[0032] Step 1, Mixing LiNi x Co y Mn 1-x-y O2 positive electrode material, chromium oxalate, and ethanol to obtain a slurry;

[0033] Step 2, heating the slurry until the ethanol is completely volatilized to obtain solid particles; drying the solid particles to obtain a precursor;

[0034] Step 3, grinding and mixing the precursor and the NiTiO3 material, and then calcining in an air atmosphere;

[0035] Among them, 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3.

[0036] The core of the prepared positive electrode material is LiNi x Co y Mn 1-x-y O2, the first coating layer is Cr2O3, and the second coating layer is NiTiO3. Cr2O3 is first grown in situ on the surface of the positive electrode material to obtain LiNi x Co y Mn 1-x-y O2 / Cr2O3 precursor material, and then NiTiO3 is coated on the surface of the precursor material by mechanical mixing. The structure of the prepared positive electrode material is more stable and firm, reducing the possibility of the coating layer falling off and improving the cycle stability of the positive electrode material. The combination of Cr2O3 and NiTiO3 can play a synergistic effect. First, the coating strategy itself can enhance the structural stability of the positive electrode material to resist structural changes during charging and discharging, which is conducive to maintaining high capacity and improving the cycle stability of the battery; secondly, Cr2O3 grows in situ on the surface of the matrix material, and the structure is more firm.

[0037] In other embodiments, in addition to the above preparation method, the Cr2O3 material and the NiTiO3 material can be coated on the LiNi x Co y Mn 1-x-y O2 positive electrode material surface.

[0038] Preferably, in step 1, the LiNi in the slurry xCo y Mn 1-x-y The mass ratio of the O2 positive electrode material to chromium oxalate is 1:1~5%.

[0039] The amount of chromium oxalate in the slurry affects the thickness of the Cr2O3 coating layer. If the amount of chromium oxalate is too high, the Cr2O3 coating will be too thick, affecting the lithium ion deintercalation and the capacity of the positive electrode material; if the amount of chromium oxalate is too low, the Cr2O3 coating will be uneven, affecting the cycle stability.

[0040] Preferably, in step 2, the heating temperature is 50-150° C.; the drying temperature is 80-180° C., and the drying time is 1-10 hours.

[0041] Preferably, in step 3, the calcination temperature is 700-1200° C. and the calcination time is 1-5 h.

[0042] If the calcination temperature is too low, the coating effect will be affected, and it is easy for the coating material to fail to adhere tightly to the surface of the positive electrode material, or the coating will be uneven; if the calcination temperature is too high, overburning may occur, affecting the physical and electrochemical properties of the material, and thus affecting its conductivity.

[0043] Preferably, in step 3, the LiNi in the precursor x Co y Mn 1-x-y The mass ratio of O2 and NiTiO3 is 1:1~3%.

[0044] Wherein, in step 3, the NiTiO3 material can use commercially available NiTiO3, which is also prepared by the following preparation method:

[0045] Mix and stir Ni(CH3COO)2·4H2O, Ti(OC4H9)4 and ethylene glycol solution, react for a period of time and then centrifuge. Wash, dry and calcine the obtained solid matter to obtain the product.

[0046] Preferably, the molar ratio of the nickel element in Ni(CH3COO)2·4H2O and the titanium element in Ti(OC4H9)4 used to prepare the NiTiO3 material is 1:0.8-1.2.

[0047] Preferably, the drying temperature is 100-150° C. and the drying time is 10-15 hours.

[0048] Preferably, the detergent is ethanol.

[0049] Preferably, the calcination temperature is 600-1000° C., and the calcination time is 2-10 hours.

[0050] The nickel titanate particles obtained by the process provided by the present invention are finer and have better crystallinity, and can be used to coat positive electrode materials to further improve the electrochemical performance of the positive electrode materials.

[0051] In a third aspect, the present invention provides a battery.

[0052] In order to make the technical problems, technical solutions and technical advantages to be solved by the present invention more clear, they will be described in detail below with reference to specific examples, but the protection scope of the present invention is not limited to the following specific embodiments.

[0053] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0054] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in the present invention can be purchased from the market or prepared by existing methods.

[0055] The nickel titanate used in the following Examples 1-3 and Comparative Examples 1-2 was prepared by the following preparation method:

[0056] Step 1, weigh 2.48 g of Ni(CH3COO)2·4H2O and add it to 60 mL of ethylene glycol solution, and stir continuously on a magnetic stirrer until Ni(CH3COO)2·4H2O is completely dissolved.

[0057] Step 2, then add 3.4 mL Ti(OC4H9)4 and stir on a magnetic stirrer for 1 h. ;

[0058] Step 3, centrifuging the solution and washing with ethanol for 6 times. After drying in a vacuum drying oven at 60° C. for 12 h, a NiTiO3 precursor material was obtained.

[0059] Step 4, pour the precursor into the crucible, cover the pot, put it into the muffle furnace, heat it to 600°C at a rate of 5°C / min, keep it warm for 2h, and then cool it down to obtain the desired NiTiO3 material.

[0060] Embodiment 1:

[0061] A method for preparing a positive electrode material comprises the following steps:

[0062] Step 1: Mix ethanol and Cr2(C2O4)3·6H2O to obtain a mixed solution with a Cr ion concentration of 10 mmol / L, and add 10 g LiNi 0.9 Co 0.0.5 Mn 0.05 O2, and stirred for 1 h to fully mix to obtain a slurry.

[0063] Step 2: The slurry was placed in an oil bath at 120°C and heated until the ethanol was evaporated to dryness, and then the obtained solid particles were transferred to a drying oven at 120°C and dried for 12 hours to obtain LiNi 0.9 Co 0.0.5 Mn 0.05 O2 / Cr2O3 precursor.

[0064] Step 3, take 10gLiNi 0.9 Co 0.0.5 Mn 0.05 The O2 / Cr2O3 precursor was ground and mixed with 0.2 g NiTiO3, and then transferred to a muffle furnace and calcined at 900° C. in air for 3 h to obtain a NiTiO3 / Cr2O3 co-modified positive electrode material.

[0065] Figure 1 Uncoated LiNi 0.9 Co 0.0.5 Mn 0.05 SEM image of O2, Figure 1 It can be seen that LiNi 0.9 Co 0.0.5 Mn 0.05 The O2 material is a single crystal with a relatively smooth surface.

[0066] Figure 2 is a SEM image of the positive electrode material obtained in Example 1. Figure 2 It can be seen that fine particles appear on the surface of the positive electrode material after being coated with NiTiO3 and Cr2O3, which can indirectly prove that NiTiO3 and Cr2O3 have been successfully coated on the surface of the positive electrode material.

[0067] Comparative Example 1:

[0068] A method for preparing a positive electrode material comprises the following steps:

[0069] Take 10gLiNi 0.9 Co 0.0.5 Mn 0.05 O2 and 0.2gNiTiO3 were ground and mixed, and then transferred to a muffle furnace and calcined at 900°C in air for 3h to obtain the NiTiO3-coated positive electrode material.

[0070] Comparative Example 2:

[0071] A method for preparing a positive electrode material comprises the following steps:

[0072] Step 1: Mix ethanol and Cr2(C2O4)3·6H2O to obtain a mixed solution with a Cr ion concentration of 10 mmol / L, and add 10 g LiNi 0.9 Co 0.0.5 Mn 0.05O2, and stirred for 1 h to fully mix to obtain a slurry.

[0073] Step 2: The slurry was placed in an oil bath at 120°C and heated until the ethanol was evaporated to dryness, and then the obtained solid particles were transferred to a drying oven and dried at 120°C for 12 hours to obtain LiNi 0.9 Co 0.0.5 Mn 0.05 O2 / Cr2O3 precursor.

[0074] Step 3: LiNi prepared in step 2 0.9 Co 0.0.5 Mn 0.05 The O2 / Cr2O3 precursor was placed in a muffle furnace and calcined at 900°C in air for 3 h to obtain a Cr2O3-coated positive electrode material.

[0075] Embodiment 2:

[0076] A method for preparing a positive electrode material comprises the following steps:

[0077] Step 1: Mix ethanol and Cr2(C2O4)3·6H2O to obtain a mixed solution with a Cr ion concentration of 10 mmol / L, and add 10 g LiNi 0.7 Co 0.2 Mn 0.1 O2, and stirred for 1 h to fully mix to obtain a slurry.

[0078] Step 2: The slurry was placed in a 50°C oil bath and heated until the ethanol was evaporated to dryness, and then the obtained solid particles were transferred to a drying oven and dried at 80°C for 1 h to obtain LiNi 0.7 Co 0.2 Mn 0.1 O2 / Cr2O3 precursor.

[0079] Step 3: Take 10gLiNi 0.7 Co 0.2 Mn 0.1 The O2 / Cr2O3 precursor was ground and mixed with 0.1 g NiTiO3, and then transferred to a muffle furnace and calcined at 700°C in air for 1 h to obtain a NiTiO3 / Cr2O3 co-modified positive electrode material.

[0080] Embodiment 3:

[0081] A method for preparing a positive electrode material comprises the following steps:

[0082] Step 1: Mix ethanol and Cr2(C2O4)3·6H2O to obtain a mixed solution with a Cr ion concentration of 10 mmol / L, and add 10 g LiNi 0.8 Co 0.1Mn 0.1 O2, and stirred for 1 h to fully mix to obtain a slurry.

[0083] Step 2: The slurry was placed in an oil bath at 150°C and heated until the ethanol was evaporated to dryness, and then the obtained solid particles were transferred to a drying oven at 180°C and dried for 10 h to obtain LiNi 0.8 Co 0.1 Mn 0.1 O2 / Cr2O3 precursor.

[0084] Step 3, take 10gLiNi 0.8 Co 0.1 Mn 0.1 The O2 / Cr2O3 precursor was ground and mixed with 0.3 g NiTiO3, and then transferred to a muffle furnace and calcined at 1200° C. in air for 5 h to obtain a NiTiO3 / Cr2O3 co-modified positive electrode material.

[0085] Embodiment 4:

[0086] The difference from Example 1 is that the nickel titanate used in step 3 is purchased from Aladdin Chemical Reagent Network.

[0087] The positive electrode materials prepared in Examples 1 to 4 and Comparative Examples 1 to 2, LiNi 0.9 Co 0.0.5 Mn 0.05 O2 was weighed and ground according to the ratio of positive electrode material: conductive graphite: PVDF in 8:1:1, dissolved in N-methylpyrrolidone (NMP), stirred evenly to form a slurry, and then coated on the current collector aluminum foil, dried at 90°C for 12h in a blast dryer, and punched into a disc electrode with a diameter of 12mm. The disc electrode was used as the positive electrode, the metal lithium sheet was used as the negative electrode, the lithium ion secondary electrolyte was the commercially available LB-037 (1MLiPF6in DEC:EC:EMC=1:1:1Vol%) as the electrolyte, and Celgard2325 was used as the diaphragm. The LIR2032 button battery was assembled in the glove box according to the assembly sequence of the button battery.

[0088] The battery was placed in a 25°C constant temperature box, charged at a constant current rate of 0.1C to a voltage of 4.3V, then charged at a constant voltage rate of 0.01C to a cut-off value, and then discharged at 0.1C to 3V, and the cycle was repeated twice. Then the battery was charged at a constant current rate of 0.5C to a voltage of 4.3V, then charged at a constant voltage rate of 0.05C to a cut-off value, and then discharged at 0.5C to 3V. The charge and discharge capacities were recorded. The test results are shown in Figure 3 .

[0089] Depend on Figure 3 It can be seen that LiNi without coating treatment 0.9 Co 0.0.5 Mn0.05 The capacity and cycle stability of the battery assembled with O2 positive electrode materials are the lowest. The capacity and cycle stability of the battery assembled with positive electrode materials coated with NiTiO3 materials and Cr2O3 materials have been improved to a certain extent, but the overall performance is general. The capacity and cycle stability of the battery assembled with Cr2O3 / NiTiO3 positive electrode materials coated provided by the present invention are significantly improved.

[0090] The embodiments described above are only preferred specific implementation modes of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical solutions and concepts of the present invention within the technical scope of the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a positive electrode material, characterized in that: The steps include: Step 1, mixing LiNi x Co y Mn 1-x-y O2 positive electrode material, chromium oxalate, ethanol, to obtain slurry; wherein 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3; Step 2, heating the slurry until the ethanol is completely volatilized to obtain solid particles; drying the solid particles to obtain a precursor; Step 3, grinding and mixing the precursor and the NiTiO3 material, and then calcining in an air atmosphere; The prepared positive electrode material includes a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least a portion of the surface of the substrate, and the second coating layer is coated on at least a portion of the surface of the particles formed by the substrate and the first coating layer; the chemical formula of the substrate is LiNi x Co y Mn 1-x-y O2, 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3; the first coating layer is Cr2O3; the second coating layer is NiTiO3.

2. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 1, the LiNi in the slurry x Co y Mn 1-x-y The mass ratio of the O2 positive electrode material to chromium oxalate is 1:1~5%.

3. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 3, the LiNi in the precursor x Co y Mn 1-x-y The mass ratio of O2 and NiTiO3 is 1:1~3%.

4. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 2, the heating temperature is 50-150° C.; the drying temperature is 80-180° C., and the drying time is 1-10 hours.

5. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 3, the calcination temperature is 700-1200° C. and the calcination time is 1-5 hours.

6. The method for preparing the positive electrode material according to claim 1, characterized in that: In step 3, NiTiO3 material is prepared by the following method: Ni(CH3COO)2·4H2O, Ti(OC4H9)4 and ethylene glycol solution are mixed, solid-liquid separation is performed after a period of reaction, and the obtained solid material is washed, dried and calcined to obtain NiTiO3 material.

7. The method for preparing the positive electrode material according to claim 6, characterized in that: The molar ratio of the nickel element in Ni(CH3COO)2·4H2O and the titanium element in Ti(OC4H9)4 used to prepare the NiTiO3 material is 1:0.8~1.2; the calcination temperature is 600~1000℃, and the calcination time is 2~10h.

8. A positive electrode material, characterized in that The positive electrode material is prepared by the preparation method according to any one of claims 1 to 7, wherein the positive electrode material comprises a substrate, a first coating layer and a second coating layer, wherein the first coating layer is coated on at least part of the surface of the substrate, and the second coating layer is coated on at least part of the surface of the particles formed by the substrate and the first coating layer; the chemical formula of the substrate is LiNi x Co y Mn 1-x-y O2, 0.7≤x<1, 0≤y≤0.2, 0<1-xy≤0.3; the first coating layer is Cr2O3; the second coating layer is NiTiO3.

9. A battery, characterized in that: A positive electrode material comprising the preparation method described in any one of claims 1 to 7.

Citation Information

Patent Citations

  • Positive electrode material of lithium ion battery and preparation method thereof

    CN111430679A